Rectal Indomethacin Is Protective against Pancreatitis after Endoscopic Retrograde Cholangiopancreatography: Systematic Review and Meta-Analysis - Xingkang He; Wenfang Zheng; Yue Ding; Xia Tang; Jianmin Si; Lei-min Sun (Gastroenterology Research and Practice)
Background and Aim. Rectal indomethacin was reported to be effective for postendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) prophylaxis. However, the preventive effect of indomethacin for average-risk patients remains unclear. Recently, some conflicting evidence was addressed by recent articles. We aimed to determine the protective role of indomethacin in PEP based on the latest available literature. Methods. A systematic literature search was conducted using PubMed, Embase, Web of Science, and the Cochrane Library to identify related articles published before October 2016. Studies that evaluated the administration of indomethacin in the prevention of PEP were included in the analysis. We adopted a random-effects model to calculate the overall relative risk (RR) and 95% confidence interval (CI). Results. Ten trials from an initial search were finally included in the meta-analysis. The administration of rectal indomethacin significantly reduced the incidence of PEP in consecutive ERCP population (RR, 0.63; 95% CI, 0.50–0.77). There was no significant heterogeneity across included studies (I2=14.2%, P=0.31). Further subgroup analyses also revealed that rectal indomethacin could protect the individuals at high and average risks and reduced severity of PEP. Pre-ERCP administration of indomethacin seemed to be better than the post-ERCP given. There was no evidence of significant publication bias. Conclusions. Rectal administration of indomethacin is an effective approach to prevent the incidence of PEP in both high- and average-risk populations undergoing ERCP. However, more high-quality RCTs are needed to further investigate the optimal timing for the administration of indomethacin.